Improving Students’ Reading Skills in Recount Texts Through the Natural Approach (EUFONI: Journal of Language, Literary, and Cultural Studies, 2024)
This study focuses on teaching reading of recount texts using the Natural Approach, based on the theory proposed by Krashen and Terrell (1983). The primary objectives were to determine the effectiveness of the Natural Approach in teaching recount text reading and to assess the improvement in reading skills among eighth-grade students at MTs Al-Makmur Parung Panjang. A pre-experimental research design was employed, utilizing a one-group pre-test and post-test framework, which included three meetings with treatment sessions. The study incorporated both qualitative and quantitative research methods for data collection. A total of 33 students from class 8.1 participated in the study. Qualitative data were gathered through observation guidelines during the recount text reading sessions, while quantitative data were obtained by analyzing the students' scores from the pre-test and post-test. The results were derived from a five-question essay test administered before and after the treatment. The mean scores demonstrated significant improvement: the pre-test average was 4.36, while the post-test average increased to 8.06. This improvement is further supported by the t-test results, which indicated a t-value of 12.737, exceeding the t-table value of 2.036. Thus, the alternative hypothesis was accepted, and the null hypothesis was rejected. Based on the findings, the use of the Natural Approach effectively enhances reading skills among eighth-grade students at MTs Al-Makmur Parung Panjang, indicating that this approach is a valuable method for improving students' reading proficiency.